Interactions between radial electric field, transport and structure in helical plasmas - Katsumi Ida (Вопросы атомной науки и техники, 2006)
Control of the radial electric field is considered to be important in helical plasmas, because the radial electric field and its shear are expected to reduce neoclassical and anomalous transport, respectively. Particle and heat transport, that determines the radial structure of density and electron profiles, sensitive to the structure of radial electric field. On the other hand, the radial electric field itself is determined by the plasma parameters. In general, the sign of the radial electric field is determined by the plasma collisionality, while the magnitude of the radial electric field is determined by the temperature and/or density gradients. Therefore the structure of radial electric field and temperature and density are strongly coupled through the particle and heat transport and formation mechanism of radial electric field. Interactions between radial electric field, transport and structure in helical plasmasis discussed based on the experiments on Large Helical Device.